The Role of Dermoscopy in Rosacea Diagnosis. A Review of the Literature - Al-Refu, Khitam; Samaro, Saed; Al-Lala, Heba; Ismail, Abdallah; Rayyan, Deema; Al-Momani, Ahmad (Jordan Medical Journal, 2025)
Background. Rosacea is a chronic inflammatory skin disorder that manifests as persistent facial redness, papules, and pustules on the background of telangiectasia. Diagnosing it is often challenging because its symptoms overlap with skin conditions like seborrheic dermatitis and acne. Accurate diagnosis is important for effective management. Aims. This review aims to assess the role of dermoscopy as a non-invasive diagnostic tool in improving the accuracy of rosacea diagnosis and its subtypes. Materials and Methods. The review focuses on the characteristic follicular and vascular features detectable through dermoscopy and identifies key dermoscopic features of rosacea, such as polygonal vessels, follicular plugging, and Demodex mites. These findings were assessed in the context of differentiating between the various subtypes of rosacea, including papulopustular, erythematotelangiectatic, phymatous, and granulomatous. Results. The review revealed that dermoscopy significantly enhances the diagnostic precision of rosacea by revealing specific vascular and follicular patterns that are otherwise difficult to detect through clinical observation alone—furthermore, dermoscopy aids in classifying rosacea into its specific subtypes. This improved diagnostic accuracy can lead to better clinical outcomes and more effective treatment monitoring for patients with rosacea.